2014
DOI: 10.1186/s40345-014-0016-7
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic lithium treatment and cognitive performance in patients with a long history of bipolar illness: no simple answers in complex disease-treatment interplay

Abstract: Cognitive impairment in patients with bipolar disorder (BD) is not restricted to symptomatic phases. It is also present in euthymia. There is evidence of differences in the brain’s structure between bipolar patients and healthy individuals, as well as changes over time in patients. Lithium constitutes the gold standard in long-term prophylactic treatment. Appropriate therapy that prevents new episodes improves the disease’s course and reduces the frequency of harmful outcomes. Interestingly, preclinical data s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 49 publications
2
24
0
Order By: Relevance
“…On the other hand, a meta‐analysis examining the trajectory of cognitive impairment in bipolar disorder indicated that bipolar patients' performance on 14 cognitive measures remained stable, but the mean follow‐up period was relatively short (4.62 years) . Also, Pfennig et al showed that lithium‐treated patients with a long‐standing bipolar disorder and controls did not differ significantly in neurocognitive performance in overall cognitive function and verbal learning, recall, and recognition, regardless of whether lithium was part of their long‐term treatment. Very recently, Seelye et al demonstrated a steeper aging‐related decline specific to cognitive control processes of cognitive flexibility in bipolar adults to nonbipolar adults.…”
Section: Bipolar Disorder To Dementiamentioning
confidence: 99%
“…On the other hand, a meta‐analysis examining the trajectory of cognitive impairment in bipolar disorder indicated that bipolar patients' performance on 14 cognitive measures remained stable, but the mean follow‐up period was relatively short (4.62 years) . Also, Pfennig et al showed that lithium‐treated patients with a long‐standing bipolar disorder and controls did not differ significantly in neurocognitive performance in overall cognitive function and verbal learning, recall, and recognition, regardless of whether lithium was part of their long‐term treatment. Very recently, Seelye et al demonstrated a steeper aging‐related decline specific to cognitive control processes of cognitive flexibility in bipolar adults to nonbipolar adults.…”
Section: Bipolar Disorder To Dementiamentioning
confidence: 99%
“…Lithium has received more clinical assessment of its neuroprotective capacity than any other agent, most notably in bipolar disorder. Crosssectional studies of bipolar patients have associated lithium treatment with: (a) attenuation of cortical grey matter loss and (b) maintained white matter integrity (Table 1) (Giakoumatos et al, 2015;Gildengers et al, 2015;Hajek et al, 2012Hajek et al, , 2014Hartberg et al, 2015;Pfennig et al, 2014;Poletti, Locatelli, Radaelli, Colombo, & Benedetti, 2014;Simonetti et al, 2016;van Erp et al, 2012;Zung et al, 2016), though few have correlated lithium's structural benefits with a similar improvement in brain function.…”
Section: Lithiummentioning
confidence: 99%
“…Therefore, a cautionary approach in using centrally active medication during the formative years of the nervous system is wise, but at the same time, it is also important to evaluate the potential benefits and adverse effects of an effective treatment such as lithium, and research its use in children that may be suffering from a serious form of the same illness. This is particularly important because recent evidence suggests that lithium may have several benefits including neuroprotective effects, and a delay in the initiation of treatment has been found to be associated with poor outcomes …”
Section: Introductionmentioning
confidence: 99%
“…This is particularly important because recent evidence suggests that lithium may have several benefits including neuroprotective effects, and a delay in the initiation of treatment has been found to be associated with poor outcomes. [8][9][10] Therefore, as a joint effort between IGSLi (www.igsli.org) and the ISBD Task Force on Lithium Treatment (www.isbd.org/active-taksforces), the objective of this study was to summarize the available evidence concerning the effectiveness and tolerability of lithium in the treatment of paediatric mania using a systematic review.…”
Section: Introductionmentioning
confidence: 99%